Analysis of diarrhea incidence based on demographic characteristics and hygiene behavior of adults in Indonesia and Taiwan - Firdaus Firdaus; Rahmadaniar Aditya Putri; Siti Damawiyah; Faridah Umamah; Difran Nobel Bistara (PAGEPress Publications, 2024)
Diarrhea is a common manifestation of gastroenteritis, affecting both children and adults globally. Subsequently, gastroenteritis is particularly prevalent in developing countries such as Indonesia and Taiwan. This research aimed to analyze the incidence of diarrhea based on socio-demographics and personal hygiene in Indonesia and Taiwan. The method used in this research was a quantitative design with a cross-sectional approach, and the data collection involved interviews with adults, using a structured questionnaire. The primary goal of the analysis was to examine the bivariate relationships between each variable and the incidence of diarrhea, and the logistic regression test was applied for the multivariate test. A result from Taiwan respondents, the statistical tests showed significant relationships with age with a p-value of 0.009, education with a p-value =0.010, and personal hygiene with a p-value =0.010. Factors that influenced diarrhea in Indonesia were education with a p-value =0.038 and income with a p-value =0.08. In summary, several socio-demographics and personal hygiene practices played a significant role in the incidence of diarrhea. The differences in results obtained from Taiwan and Indonesia were attributed to differing respondent characteristics, emphasizing the importance of promoting clean and healthy behaviors, including handwashing with soap before eating and maintaining a clean environment, as effective measures to prevent diarrhea.